A New Technique for Augmentation Rhinoplasty Using Hybrid Autologous Grafts with Septal Extension Grafts in Asian Patients - Mizuno, Tsutomu (Facial Plastic Surgery, 2019)
Augmentation rhinoplasty is commonly performed to raise the nasal dorsum in Asian individuals. However, materials used for dorsal augmentation are associated with various surgical challenges and complications. In this article, the authors present a novel dorsal augmentation technique combining hybrid autologous costal grafts with septal extension grafts. The records of 28 patients (19 women and 9 men; mean age: 27 years; range: 18–43 years) who underwent augmentation rhinoplasty (primary or revision) with our novel technique from December 2007 to December 2016 were retrospectively reviewed. Our technique included septal extension grafts for nasal tip projection and hybrid costal cartilage grafts, with a solid boat-shaped portion for bony dorsum augmentation and a fascia-wrapped diced cartilage graft for cartilaginous dorsum augmentation. Objective and subjective outcomes and complications were evaluated. Anthropometric parameters were measured on facial photographs to evaluate surgical outcomes in the 15 primary cases. Objective anthropometric measurements revealed successful augmentation of all nasal parameters. The nasal tip was mobile and comfortable in all patients. Among the 28 patients, 12 (42.9%) were very satisfied, 10 (35.7%) were satisfied, and 6 (21.4%) were unsatisfied with surgical results and required revision surgery. No immediate postoperative complications occurred. Ten (35.7%) patients experienced graft-related complications, including visibility or warping of the solid graft, supratip depression, and caudal deviation of the septal extension graft. None of these complications was serious. Augmentation rhinoplasty using hybrid autologous costal grafts with septal extension grafts allows dorsal augmentation with suitable graft material for each recipient site and can achieve successful outcomes in Asian patients.
Keywords: nasal dorsal augmentation; septal extension graft; Asian rhinoplasty